2017
DOI: 10.1002/gj.3023
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology, geochemistry, and zircon Hf isotopes of the late Permian–early Triassic Wuma intrusions in the Erguna Block, northeast China: Petrogenesis and implications for tectonic setting and crustal growth

Abstract: The Wuma magmatic suite is a group of large granite plutons and small diorite stocks in the Erguna Block, northeast China. These intrusions were emplaced along the Mongol–Okhotsk Suture Zone during the late Permian–early Triassic (253–248 Ma). Significant chemical and isotopic diversity within the granites and diorites suggests variable formation conditions and the involvement of multiple magmatic sources. The granitic intrusions are dominantly characterized by moderate to large, uniform light rare earth eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 76 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…The Xinghuadukou Complex is mostly found in the Erguna Block, the northern most segment of the NE China, which is bounded by the Mongol‐Okhotsk Ocean (MOO) suture zone to the north and the Xinlin‐Xiguitu suture to the south. In this region, recent studies reported voluminous Palaeozoic‐Mesozoic igneous rocks related to the MOO tectonic regime (Gou, Sun, Hou, & Yang, ; Gou, Sun, Ren, Hou, & Yang, ; Li et al, ; Liu, Li, He, Huangfu, & Liu, ; Sun, Gou, et al, ; Tang et al, ; Tang, Xu, Wang, Zhao, & Li, ; Tang, Xu, Wang, Zhao, & Wang, ; Wang, Tang, Xu, & Wang, ) and the ophiolitic melange, high‐pressure metamorphic rocks, and collisional granitoids related to the evolution of the Palaeo‐Asian Ocean along the Xinlin‐Xiguitu suture, which constrained the timing of this suture (Feng et al, ; Feng et al, ; Feng et al, ; Miao, Zhang, & Jiao, ; Zhao, Takasu, Liu, & Li, ; Zhou et al, ). However, study on the Xinghuadukou Complex is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The Xinghuadukou Complex is mostly found in the Erguna Block, the northern most segment of the NE China, which is bounded by the Mongol‐Okhotsk Ocean (MOO) suture zone to the north and the Xinlin‐Xiguitu suture to the south. In this region, recent studies reported voluminous Palaeozoic‐Mesozoic igneous rocks related to the MOO tectonic regime (Gou, Sun, Hou, & Yang, ; Gou, Sun, Ren, Hou, & Yang, ; Li et al, ; Liu, Li, He, Huangfu, & Liu, ; Sun, Gou, et al, ; Tang et al, ; Tang, Xu, Wang, Zhao, & Li, ; Tang, Xu, Wang, Zhao, & Wang, ; Wang, Tang, Xu, & Wang, ) and the ophiolitic melange, high‐pressure metamorphic rocks, and collisional granitoids related to the evolution of the Palaeo‐Asian Ocean along the Xinlin‐Xiguitu suture, which constrained the timing of this suture (Feng et al, ; Feng et al, ; Feng et al, ; Miao, Zhang, & Jiao, ; Zhao, Takasu, Liu, & Li, ; Zhou et al, ). However, study on the Xinghuadukou Complex is limited.…”
Section: Introductionmentioning
confidence: 99%